A Novel Pyroptosis-Related Gene Signature for Prognostic Prediction of Head and Neck Squamous Cell Carcinoma - Qian X (Dove Medical Press, 2021)
Xiaoyu Qian,1,* Jian Tang,1,* Yongquan Chu,1 Ziqiang Chen,1 Liang Chen,1 Chao Shen,1 Lin Li2 1Department of Head and Neck Surgery, The First Hospital of Jiaxing, The Affiliated Hospital of Jiaxing University, Jiaxing, Zhejiang, People’s Republic of China; 2Department of Nuclear Medicine Clinic, The First Hospital of Jiaxing, The Affiliated Hospital of Jiaxing University, Jiaxing, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lin Li Tel +86-18367300158Email sh0wrain@126.comBackground: Head and neck squamous cell carcinoma (HNSCC) is an extremely heterogeneous malignant cancer with poor prognosis. Pyroptosis is defined as a novel inflammation-dependent programmed cell death. However, the pyroptosis-associated gene expression in HNSCC and their relationship with prognosis are still indistinct.Material and Methods: We acquired the mRNA expression information of HNSCC patients from publicly available TCGA and GEO databases. We compared the tumor issues and adjacent normal tissues in terms of the gene expression for the purpose of identifying differentially expressed genes (DEGs). Based on these genes, we established a risk signature by the LASSO Cox regression in the TCGA cohort and validated the results in a GEO cohort. We also verified the levels of relevant mRNA expression in the model by RT-qPCR analysis. Eventually, functional enrichment approach was carried out to explore the potential mechanisms.Results: Our team found a total of 18 differentially expressed genes (DEGs) between the HNSCC and healthy samples, and 4 DEGs displayed a remarkable association with the overall survival (OS) (P < 0.05). A 4-gene signature was constructed, presenting beneficial forecast power in both TCGA and GEO cohorts. Our team categorized patients into a group with high risk and another group with low risk as per the average risk value of the 4-gene feature. The individuals in the low risk group displayed a notably greater OS compared with the high risk one (P < 0.01). The Cox regression study demonstrated the independent forecast capability of the risk score. The receiver operating characteristic approach facilitated the verification of the forecast function of the gene signature. Posterior to verification, 4 genes were aberrantly expressed in the HNSCC and healthy samples. Functional study displayed that these groups presented diverse immunity conditions.Conclusion: Pyroptosis-associated genes are pivotal for the prognosis of HNSCC and can serve as potential therapeutic targets.Keywords: pyroptosis, head and neck squamous cell carcinoma, overall survival, risk signature, prognosis